2017
DOI: 10.1016/j.worlddev.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Effects of Growth and Public Expenditures in Africa: Estimates for Tanzania and Rwanda

Abstract: In this paper we explore the effects of fiscal policies and growth on measures of the household welfare across the distribution of expenditure for two countries in Africa: Rwanda and Tanzania. We explore issues of inefficiency in government expenditures and dilution of growth benefits among the better off sectors of the population in these two countries (in lieu of the poor sectors) by looking at the effects within a country and across different groups of households and administrative entities. We exploit vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Additional evidence showed that employment is key to attaining a higher income and improving access to infrastructure (Batabyal, 2013). In Tanzania and Rwanda, Almanzar and Torero (2017) employed the fixed effect (FE) and quantile regression to investigate the impact of fiscal spending and growth on household welfare across public-expenditure targeted groups. They revealed that the mean expenditure growth benefited the top expenditure groups and that the richest segments of the population benefited the most from growth.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Additional evidence showed that employment is key to attaining a higher income and improving access to infrastructure (Batabyal, 2013). In Tanzania and Rwanda, Almanzar and Torero (2017) employed the fixed effect (FE) and quantile regression to investigate the impact of fiscal spending and growth on household welfare across public-expenditure targeted groups. They revealed that the mean expenditure growth benefited the top expenditure groups and that the richest segments of the population benefited the most from growth.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…This study aims to generate evidence that can help the Rwandan government to design agricultural policies and expenditure portfolios that reflect today's broader food system focus, embody multiple development goals, and promote cost-effective market-led transformation. The study builds on prior research on Rwanda that assesses the impact of public expenditure on issues such as agricultural research and development (R&D) (Al-Mamun et al 2018), urbanization and agglomeration (World Bank and GoR 2020), and fiscal spending more generally (Almanzar and Torero 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This article also contributes to various strands of literature. First, the article contributes to the recent literature on the roles of social‐sector PE in general (e.g., Almanzar & Torero, 2017; Anderson et al., 2017, 2018) as well as PE for agriculture (Fan & Zhang, 2008; Fan et al., 2000; Mogues & Benin, 2012; Mogues & Olofinbiyi, 2020) by providing microlevel evidence. By directly estimating the effects of SNPE, the article also partly contributes to the literature on fiscal decentralization and economic growth in developing countries (e.g., Bird & Vaillancourt, 2008; Martinez‐Vazquez & McNab, 2003).…”
Section: Introductionmentioning
confidence: 99%